Do honesty and high ethical standards really pay? - Fullmer, Eric L. (International journal of value-based management, 1992)
This question is considered from the personal side as well as the organizational side. An attempt is made to avoid purely philosophical arguments, but instead to list specific ways honesty and high ethical standards either do pay or do not pay. No absolute conclusion, “yes” or “no”, can be drawn since there are times and situations when, if not managed carefully, honesty and high ethical standards can work to the detriment of both the individual and the corporation. Sources of honesty and high ethical standards are also examined from both the individual and organizational perspectives. The best situation is when there is strong individual and corporate commitment buttressed by supporting structures that balance the needs of individuals, their companies, and society as a whole.